Dispersers shape fruit diversity in Ficus (Moraceae) - Lomascolo, Silvia Beatriz (2010)
Seed dispersal by vertebrates is one of the most common and important plant-animal mutualisms, involving an enormous diversity of fruiting plants and frugivorous animals. Even though plant reproduction depends largely on seed dispersal, evolutionary ecologists have been unable to link co-occurring traits in fruits with differences in behavior, physiology, and morphology of fruit-eating vertebrates. Hence, the origin and maintenance of fruit diversity remains largely unexplained.Using amultivariate phylogenetic comparative test with unbiased estimates of odor and color in figs, we demonstrate that fruit traits evolve in concert and as predicted by differences in the behavior, physiology (perceptive ability) and morphology of their frugivorous seed dispersers. The correlated evolution of traits results in the convergence of general appearance of fruits in species that share disperser types. Observations at fruiting trees independently confirmed that differences in fig traits predict differences in dispersers. Taken together, these results demonstrate that differencesamong frugivores have shaped the evolution of fruit traits. More broadly, our results underscore the importance of mutualisms in both generating and maintaining biodiversity.